2021
DOI: 10.1212/nxg.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

WGS and RNA Studies Diagnose Noncoding DMD Variants in Males With High Creatine Kinase

Abstract: ObjectiveTo describe the diagnostic utility of whole-genome sequencing and RNA studies in boys with suspected dystrophinopathy, for whom multiplex ligation-dependent probe amplification and exomic parallel sequencing failed to yield a genetic diagnosis, and to use remnant normal DMD splicing in 3 families to define critical levels of wild-type dystrophin bridging clinical spectrums of Duchenne to myalgia.MethodsExome, genome, and/or muscle RNA sequencing was performed for 7 males with elevated creatine kinase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…However, two other sequences were found to correspond to regions 650 bp upstream (2 split-reads) and 70 kb downstream (3 split-reads), suggesting multiple potential fusion transcripts. We confirmed the presence of this rearrangement with the original authors through private correspondence, who independently discovered it using whole genome sequencing and recently reported it in Waddell et al [ 45 ].
Fig.
…”
Section: Resultssupporting
confidence: 83%
“…However, two other sequences were found to correspond to regions 650 bp upstream (2 split-reads) and 70 kb downstream (3 split-reads), suggesting multiple potential fusion transcripts. We confirmed the presence of this rearrangement with the original authors through private correspondence, who independently discovered it using whole genome sequencing and recently reported it in Waddell et al [ 45 ].
Fig.
…”
Section: Resultssupporting
confidence: 83%
“…However, two other sequences were found to correspond to regions 650bp upstream (2 split-reads) and 70kb downstream (3 split-reads), suggesting multiple potential fusion transcripts. We confirmed the presence of this rearrangement with the original authors through private correspondence, who independently discovered it using whole genome sequencing and recently reported it in Waddell et al, 2021 45 .…”
Section: Mintie Identifies Novel Splicing and Transcribed Structural Variants In Rare Diseasesupporting
confidence: 82%
“…4,5 Waddel et al using skeletal muscle biopsies reveals that normal dystrophin level ;15 ± 2% correlates to the milder spectrum of dystrophinopathies (i.e., myalgia without overt weakness), ;10 ± 2% levels of dystrophin predicts a Becker muscular dystrophy phenotype with mild weakness and cardiac involvement, and 0%-5% levels of dystrophin results in severe Becker muscular dystrophy or DMD. 2 These predictions are in line with early studies in which level of dystrophin 29%-57% of normal was shown to be sufficient to avoid muscle weakness in X-linked dilated cardiomyopathy families. 6 The novelty in the approach by Waddel et al is the estimate of normal dystrophin vs the amount of internally deleted dystrophin able to modulate the phenotype.…”
supporting
confidence: 85%
“…After being the first muscular dystrophy in which the disease gene has been identified, it is now the first muscular dystrophy to be treated, in some cases, with personalized, dystrophin-restoring therapy. 1 In spite of these tremendous advancements in the treatment of DMD, in this issue of Neurology ® Genetics, Waddel et al 2 represent the challenges in achieving a genetic diagnosis in a cohort of male patients with elevated serum creatine kinase, dystrophin protein studies suggesting an underlying dystrophinopathy, yet normal multiplex ligation-dependent probe amplification and exomic sequencing.…”
mentioning
confidence: 99%
See 1 more Smart Citation